EFFECT OF FEEDING PANICUM MOMBASA GRASS ON PRODUCTIVE TRAITS AND CARCASS CHARACTERISTICS OF LOCAL CROSS BREED GOATS - & et al., Al-Jorani (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
The aim of this research was to study the effect of feeding of goat kids on Panicum Mombasa grass on productive traits, carcass characteristics and meat production. 25 of local cross breed male goat kids; average weight 18.3 kg were divided randomly to five treatments, the first one T1 was fed with wheat straw, T2 green alfalfa, T3 green Panicum Mombasa, T4 alfalfa hay and T5 Panicum Mombasa hay. Animals reared in single cages for two weeks as a preliminary period, the experiment period lasted for 70 days. Concentrate diet provided with 3% of body weight, roughage feeds provided freely. At the end of the experiment, three animals were slaughtered from each treatment randomly, data showed no positive effects were observed for feeding the Punicum Mombasa grass when compared with the traditional roughages feed used in Iraq for most of the productive traits and the carcasses and meat characteristics studied. At the same time, no negative effects were reported on the Punicum Mombasa feed in those traits and characteristics.